2007
DOI: 10.4319/lo.2007.52.5.2199
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic isotope effect and biochemical characterization of form IA RubisCO from the marine cyanobacterium Prochlorococcus marinus MIT9313

Abstract: In an effort to better understand the factors influencing carbon fixation by Prochlorococcus, and to elucidate the effects of these cyanobacteria on the ocean carbon cycle, the kinetic parameters and isotopic discrimination of form IA ribulose 1,5-bisphosphate carboxylase/oxygenase (RubisCO) from Prochlorococcus marinus MIT 9313 were determined. The RubisCO genes (cbbL and cbbS) were cloned and expressed in Escherichia coli. Enzyme was purified via ammonium sulfate precipitation, and the optimum pH and tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 36 publications
5
61
0
Order By: Relevance
“…Because of this multiplicity of factors, phytoplankton d 13 C cannot be precisely or quantitatively used as a proxy for primary production or CO 2 concentrations [Laws et al, 1995]. In addition, different forms and subtle differences in the same forms of Rubisco mean that different phytoplankton species have different values of e f [Scott et al, 2007]. Phytoplankton growth rates, cell size, cell shape, and the potential use of carbon concentrating mechanisms all affect the balance between c i and c e , allowing for greater or less extent of the carbon isotope fractionation associated with CO 2 fixation by Rubisco to be expressed (see equation (1)) [Laws et al, 1995;Rau et al, 1996Rau et al, , 1997Rau et al, , 2001.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of this multiplicity of factors, phytoplankton d 13 C cannot be precisely or quantitatively used as a proxy for primary production or CO 2 concentrations [Laws et al, 1995]. In addition, different forms and subtle differences in the same forms of Rubisco mean that different phytoplankton species have different values of e f [Scott et al, 2007]. Phytoplankton growth rates, cell size, cell shape, and the potential use of carbon concentrating mechanisms all affect the balance between c i and c e , allowing for greater or less extent of the carbon isotope fractionation associated with CO 2 fixation by Rubisco to be expressed (see equation (1)) [Laws et al, 1995;Rau et al, 1996Rau et al, , 1997Rau et al, , 2001.…”
Section: Resultsmentioning
confidence: 99%
“…One possibility is for the d 13 C differences to be related to the species of diatoms preserved in the sediments. The size, surface to volume ratio, growth rate, and specifics of the carbon fixing enzyme, Rubisco, for each species leave room for differences in the d 13 C of different phytoplankton growing under different conditions [Laws et al, 1995;Rau et al, 1996Rau et al, , 1997Rau et al, , 2001Popp et al, 1998;Hofmann et al, 2000;Scott et al, 2007]. It may very well be that the higher d 13 C values of cores from the Pacific and Indian sectors are tied to the solid predominance of F. kerguelensis in the sediments there, something which is not true in core PS 1786 -1 from the Scotia Sea where F. kerguelensis makes up only between 10 and 45% of the diatom assemblage (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…These differences in K CO2 values may reflect differences in the intrinsic properties of the two RubisCO species. Scott et al (35) reported a remarkably high K CO2 for recombinant Prochlorococcus marinus MIT9313 RubisCO expressed in Escherichia coli, suggesting that all members of the genus Prochlorococcus may contain particularly inefficient RubisCO enzymes. It is also possible that the low turnover number of the carboxysome-bound P. marinus MED4 CsoSCA, which rapidly supplies RubisCO inside the carboxysome with its substrate, CO 2 , limits the catalytic performance of RubisCO and may explain its high apparent K CO2 .…”
Section: Discussionmentioning
confidence: 99%
“…S2). A further increase of K m for Rubisco to 750 mM, the value obtained by Scott et al (2007), degrades the model fit further, with the most notable discrepancy being a higher modeled internal C i pool at low external C i (Supplemental Fig. S2).…”
Section: Modelingmentioning
confidence: 99%